The Effect of Vitamin D Levels in Multisystem Inflammatory Syndrome in Children - Kan, Ahmet; Türe, Mehmet; Akın, Alper; Yılmaz, Kamil; Sürücü, Mehmet; Ünal, Edip; Şen, Velat; Üzel, Veysiye Hülya (Journal of Pediatric Infectious Diseases, 2022)
Objective Multiple factors being overweight, asthmatic, or being of Asian or black ethnic origins have been reported vis-à-vis the “multisystem inflammatory syndrome in children” (MIS-C). There is an association between these conditions and vitamin D deficiency, which explains why MIS-C is more common in these patients. In the present study, we attempted to retrospective evaluate the 25-hydroxy vitamin D levels of patients with MIS-C, its association with acute phase reactants, its treatment, and clinical status.Methods Patients aged between 1.5 months to 18 years with MIS-C were included in the study. All of the laboratory parameters, treatment, and response to the treatment were evaluated retrospectively. Two groups were formed. Patients had 25‐hydroxycholecalciferol D vitamin < 20 ng/mL in group 1 and ≥ 20 ng/mL in group 2.Results A total of 52 patients were included in the study. There was no statistical difference between groups in terms of acceptance of the intensive care unit treatment (p = 0.29) and response to the first-line treatment (p = 0.56). A lower median lymphocyte count (p = 0.01) and a higher median C-reactive protein (p = 0.04) and procalcitonin (p = 0.01) with N-terminal pro-B-type natriuretic peptide (p = 0.025) values were found in group 1.Conclusion Vitamin D deficiency was associated with an increased inflammatory response in children with MIS-C. More studies are required to determine the potential impact of vitamin D deficiency on the clinical outcome of MIS-C.
Keywords: multisystem inflammatory syndrome; vitamin D; inflammation parameters